The construction of substructures / Norshahira Che Soh - Che Soh, Norshahira (Universiti Teknologi MARA, Perak, 2019)
Substructure is an under laying or supporting the structure to the superstructure which it is below ground level. This report are briefly described and explain about elements of sub structure and how to construct it for the construction of single terraced and detached house. sub structure will include the ground beam and foundation which is transmit the load to the underneath sub soil. The objective of this report is to learn about the method of construction and installation of sub structure. Through showing the construction of sub structure, this report is also highlights the method for install the elements of sub structure. For complete this report also needed a several method such as interview, observation, internet searching and reference from another sources.